Genotyping Tinea Capitis Fungi and Evaluate the Antifungal Activity of Plant Extract in Vitro - Hiba Jabur Sallal1 , Zaidan Khlaif Imran2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Tinea capitis is a prevalent superficial fungal infection seen in developing nations predominantly in child, the aim of this study included isolating and identification of Tinea capitis fungi isolated from clinical samples who attenuate the outpatient clinics and other samples were collected from soils of barber shops, homes and mosques in Babylon / Hilla Province. 120 hairs, scales and soil were 80 clinical samples (hairs and scales), 30 soil samples, and 10 hair samples as control group. The results showed that: numbers of dermatophytes fungi were identified based on microscopic and Molecular criteria. T. mentagrophytes, T. tonsurans, M. audounii, M. canis. Also non dermatophytes fungus was Chaetomium globosum. Also three yeast species were identified: Candida albicans, Candida parapsilosis, Malassezia spp. based on molecular assays. The antimicrobial activity of plant extract antifungal shown, Capparis spinosa plant has highly antifungal activity shown inhibition on dermatophytes, followed by Furcraea foetida shown inhibition compare with activity of Fluconazole in vitro